Pengembangan Media Pembelajaran Flipbook Untuk Materi Sistem Koordinasi Berorientasi budaya lokal Pada Pelajaran Biologi SMA - Ni Wayan Febrianti; Arnyana Ida Bagus Putu; Purnama Bestari Ida Ayu (Jurnal Pendidikan Biologi Undiksha, 2022)
The purpose of this research is to develop flipbook learning media based on local culture with valid and practical coordination system materials. The research was conducted on students of class XI SMAN 1 Susut. Development using the ADDIE model. The product created in this research displays components such as videos, brief explanations, pictures, practice questions and quizzes. Local culture-based flipbook contains examples of local culture in each sub-material. The validity test in this study was carried out by material experts, media experts and linguists. The practicality test was carried out by 5 biology teachers and 12 class XI students of SMAN 1 Susut. Data analysis was carried out using qualitative and quantitative descriptive methods to determine the feasibility and practicality of the developed flipbook. The results showed that: (1) The results of each stage of development created a product in the form of a local culture-based flipbook on the material of the XI class coordination system, (2) The validity of the local culture-based flipbook on the coordination system material from the material expert got a score of 1 with very valid criteria, from media experts got a score of 1 with very valid criteria and from linguists got a score of 1 with very valid criteria, (3) the practicality of flipbook learning media based on local culture material for the coordination system from the teacher got a percentage of 90.88% categorized as very practical and from students got a percentage of 96 .3% are categorized as very practical, so the average practicality of flipbook learning media is 93.59% in the very practical category. Based on the results of the study of flipbook learning media based on local culture, the coordination system material developed was very valid and very practical to be used as teaching material for the XI class coordination system material at SMAN 1 Susut.